PENGEMBANGAN TEORI HUMANISTIK ABRAHAM MASLOW DAN CARL ROGERS MENGENAI BULLYING SERTA IMPLIKASINYA PADA MADRASAH IBTIDAIYAH - Setyaningrum, Putri Nadha; Arifi, Ahmad; Hatta, Jauhar (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2025)
This study discusses the development of Abraham Maslow and Carl Rogers' humanistic theory in the context of bullying and its implications for Madrasah Ibtidaiyah. The problem raised is the high prevalence of bullying, including in the world of education. The problem of bullying among students has become a global issue that has received serious attention. This study uses a library research method. Data were collected through the process of selection, searching, presenting, and analyzing library materials. The purpose of this study is to analyze bullying from the perspective of the development of Abraham Maslow and Carl Rogers' Humanistic theory and its implications. The results of the study indicate that the development of Abraham Maslow and Carl Rogers' humanistic theory regarding bullying has positive implications for Madrasah Ibtidaiyah. Bullying from the perspective of the development of the theories of the two figures, we can better understand how important it is to fulfill basic human needs and form healthy interpersonal relationships in overcoming and preventing bullying behavior. Bullying is not only a detrimental social behavior, but also a manifestation of an individual's inability to fulfill their basic psychological needs, both as victims and perpetrators. By creating a safe environment, developing empathy, building a positive identity, and involving all parties in the school, bullying can be minimized, and students can grow into better individuals with noble character.